1985
DOI: 10.1071/aj84002
|View full text |Cite
|
Sign up to set email alerts
|

The Petroleum Prospectivity of the Clarence-Moreton Basin in New South Wales

Abstract: The Clarence-Moreton Basin covers an area of some 28 000 km2 in north-eastern New South Wales and south-eastern Queensland. The basin is relatively unexplored, with a well density in New South Wales of one per 1600 km2. Since 1980, Endeavour Resources and its co-venturers have pursued an active exploration programme which has resulted in the recognition of significant petroleum potential in the New South Wales portion of the basin.Previous studies indicated that the Upper Triassic to Lower Cretaceous Clarence-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Vitrinite reflectance profiles for petroleum exploration wells suggest that between 1.5 and 2.5 km of sedimentary strata have been removed from the basin (Ties et al 1985;Russell 1992). The youngest strata preserved in the basin are Late Jurassic to earliest Cretaceous and hence subsidence continued into the Cretaceous.…”
Section: Geological Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitrinite reflectance profiles for petroleum exploration wells suggest that between 1.5 and 2.5 km of sedimentary strata have been removed from the basin (Ties et al 1985;Russell 1992). The youngest strata preserved in the basin are Late Jurassic to earliest Cretaceous and hence subsidence continued into the Cretaceous.…”
Section: Geological Frameworkmentioning
confidence: 99%
“…Martin and Saxby (1982) assessed the source rock potential of 26 samples. Jackson et al (1983) presented analyses based on systematic sampling of subsidized wells and more recently Ties et al (1985) reported on the source rock potential and maturity of samples from the Shannon-1 well and adjacent areas. The results of these studies may be summarized as follows: (i) The Walloon Coal Measures have significant potential to generate oil whereas the older stratigraphic horizons are gas prone either due to overmaturity or the nature of the organic matter, (ii) Significant maturation variations encountered in the basin cannot be readily accounted for by present geothermal gradients.…”
Section: Introductionmentioning
confidence: 98%
“…Philp & Gilbert (1986) comment that extensive Permian coal measures occur in the Sydney Basin, yet there is little oil production, although analysed oil seeps suggesting a terrigenous origin are known. The Clarence-Moreton Basin lying due east of the Surat Basin, is also viewed as a possible prospect (Ties et al 1985). From preliminary analytical data the Walloon Coal Measures apparently contain Type I and Type II kerogens, whereas the underlying Marbarg Formation (early Jurassic) has Type III kerogens which are gas-prone.…”
Section: Other Possible Australian Basins With Terrestriallysourced Hmentioning
confidence: 99%
“…The Clarence Moreton Basin covers an area of about 23,000 km' , and contains up to 3.5 km of Mesozoic sediments (Ties et al 1985). It is bounded by exposed Palaeozoic rocks and exotic terrains of the Yarrol Fold Belt to the north (Yarraman and DAguilar Blocks), the Beenleigh Block to the east and the rocks of the New England Fold Belt (Texas Block) to the…”
Section: The Geological and Tectonic Features Of The Nebine Ridge Sumentioning
confidence: 99%